Tantangan dan Reformasi Sistem Pendidikan Agama Islam di Indonesia Kontemporer - Rusli, Almunauwar Bin (IAIN Manado, 2023)
This article examines the challenges and reforms of the Islamic religious education system in contemporary Indonesia. This system has experienced ups and downs related to the social situation, culture, politics, economy and even Islamic orthodoxy. The challenges of conservatism, post-nationalism and terrorism in this article are inseparable from the crisis of professional and moderate Islamic Religious Education teachers in Indonesia. Responding to ideological challenges (conservatism, post-nationalism and terrorism) like this, school principals in public education institutions have an important position and role in making improvements through the performance of PAI teachers. The reform of PAI learning in public schools, especially the high school level, needs to do three things, namely renewal in the sector of philosophical understanding, a psychological approach and cultural development. PAI teachers need to continue to encourage their students to have the character of Pancasila students. Thus, they will believe in inclusiveness, global diversity, the ability to work together. social and creative responsibility. The mainstreaming of Islamic religious education with the perspective of religious moderation in counteracting the growth of terrorist teachings driven by eschatological imagination can continue to be fought for through the arguments above.Keywords : Conservatism, Post-Nationalism, Terrorism, PAI Reform?